Increasing Growth Tiger Prawn (Penaeus monodon) Using Organic Diet of Sauropus androgynous - Awaludin Awaludin; Ira Maya Abdiani; Ahmad Arsyidi; Rukisah Rukisah (Journal of Tropical Life Science, 2020)
Sauropus androgynous contain chemical compounds that can increase the growth of tiger prawn. This study aims to determine the growth of tiger prawns after giv- ing S. androgynous leaves ethanol extract mixed in feed. The research method uses a completely randomized design (CRD) 4 treatments, three replications. Treatment with a dose of Treatment 1 (T1) Control without giving S. androgynous extract, Treatment 2 (T2) 5 gr/kg of feed, Treatment 3 (T3) 50 gr/kg of feed, Treatment 4 (T4) 100 gr/kg of feed. Proximate test results of S. androgynous extract crude pro- tein content of 10.83%, crude fiber 1.87%, crude fat 0.85%, ash content 1.94%, dry weight 93.62%, and extract material without nitrogen 78.13%. Based on the results of the study, the weight growth and growth length statistically showed significantly different (P < 0.05). The highest growth of tiger prawn at the end of the study was found in P4 by giving S. androgynous leaf extract with an average weight growth value (70.18 ± 9.57 g). While the lowest weight growth was observed in T1 with an average weight growth value (32.62 ± 7.54 g). The highest length growth was found in T4 with average length (1.19 ± 0.10 cm), while the lowest length growth was seen in T1 with average length growth (0.62 ± 0.09 cm).